Theory of single and multiple interfaces : The method of surface Green function matching - García-Moliner, Federico; Velasco, Victor R. (Singapore World Scientific, 1992)
Based on a scattering theoretic approach which effectively constitutes an extension of the Dyson or Lippman-Schwinger theories, Green functions constitute the backbone of a matching analysis.
Includes bibliographical references
Keywords: Cơ bản